DIAGNOSTIC UTILITY OF CLINICOPATHOLOGICAL CORRELATION IN OVARIAN TUMORS: AN ANALYSIS OF 200 CASES. - LAVANYA RAJAGOPAL; USHA RAVIKUMAR (International Journal of Pharma and Bio Sciences, 2015)
The ovarian tumors manifest a wide spectrum of clinical, morphological and histological features. Their complex nature, unpredictable behaviour, prognosis and varying therapeutic strategies, necessitates an accurate diagnosis. This study is undertaken to analyze the incidence, age related occurrence, clinical presentation, gross and various histopathological patterns of ovarian tumors and also to classify and categorize them according to WHO classification. This study was done in the Department of Pathology, Madurai Medical College, Madurai, during the period 2009-2013, on 200 ovarian neoplasms. Clinical history and the pathological characteristics were recorded & analyzed. The incidence of ovarian neoplasms was 8.05% and ranked second among the female genital tract malignancies. The peak age incidence was fifth decade. Mass per abdomen was the most common clinical presentation (58%). 81.5% were unilateral and 18.5% were bilateral. Surface epithelial tumors were the commonest (77.5%), sex cord stromal tumors 7.5% and germ cell tumors 11%. Out of 200 cases, benign tumors constituted 62%, borderline tumors constituted 5.5% and malignant tumors 32.5%. There were 3 cases (1.5%) of Krukenberg’s tumor. Correlation of age, clinical features, gross , various histological patterns and categorizing according to WHO classification helps in early and accurate diagnosis as well as prognosis of ovarian tumors.